Glecaprevir/Pibrentasvir in patients with hepatitis C virus genotype 1 or 4 and past direct‐acting antiviral treatment failure. Issue 4 (30th January 2018) - Poordad, Fred; Pol, Stanislas; Asatryan, Armen; Buti, Maria; Shaw, David; Hézode, Christophe; Felizarta, Franco; Reindollar, Robert W.; Gordon, Stuart C.; Pianko, Stephen; Fried, Michael W.; Bernstein, David E.; et al.
Abstract : Patients with hepatitis C virus (HCV) who have virological failure (VF) after treatment containing a nonstructural protein 5A (NS5A) inhibitor have limited retreatment options. MAGELLAN‐1 Part 2 was a randomized, open‐label, phase 3 study to evaluate the efficacy and safety of ribavirin (RBV)‐free glecaprevir and pibrentasvir (G/P; 300 mg/120 mg) in patients with chronic HCV and past VF on at least one NS3/4A protease and/or NS5A inhibitor‐containing therapy. Patients with compensated liver disease, with or without cirrhosis, and HCV genotype (GT) 1, 4, 5, or 6 were randomized 1:1 to receive 12 or 16 weeks of G/P. The primary endpoint was sustained virological response (SVR) at 12 weeks posttreatment (SVR12). Among 91 patients treated, 87 had GT1 and 4 had GT4 infection. SVR12 was achieved by 89% (39 of 44) and 91% (43 of 47) of patients who received 12 and 16 weeks of G/P, respectively. Virological relapse occurred in 9% (4 of 44) of patients treated with 12 weeks of G/P; there were no relapses with 16 weeks of treatment. Past treatment history with one class of inhibitor (protease or NS5A) had no impact on SVR12, whereas past treatment with both classes of inhibitors was associated with lower SVR12 rate. The most common adverse event (AE) was headache (≥10% of patients), and there were no serious AEs assessed as related to study drugs or AEs leading to discontinuation. Conclusion : Sixteen weeks of G/P treatment achieved a high SVR12 rate in patients with HCV GT1 infection and past failure to regimens containing either NS5A inhibitors or NS3 protease inhibitors. (Hepatology 2018;67:1253‐1260)